A rare malignancy in an uncommon location: case of a 25-year-old female patient with infiltrative vulvar basal cell carcinoma - Mercado-Figueroa, Hillary; Silva-Martinez, Jose; Pastrana-Echevarria, Itzamar; Ortiz-Orama, Alexandra (International Journal of Research in Dermatology, 2025)
Basal cell carcinoma (BCC) of the vulva accounts for less than 1% of all BCCs. Herein this report describes a case of a 25-year-old female with vulvar BCC that was presented as an ulcerated mass lesion with erythema, fissuring and bleeding in the upper region of the right labium majus. After biopsy, the histopathology results showed basal cell carcinoma, mixed nodular and infiltrative type with focal areas of squamous metaplasia confirmed by IHC staining for common BCC markers. The reasoning for this clinical case is to report the atypical presentation and unique histopathology, for future consideration as a differential diagnosis when encountering genital lesions and to contribute to an ideal treatment. Vulvar BCCs remain a rare tumor of the vulva, which has excellent prognosis if managed appropriately. Therefore, any persistent lesion in the vulvar region should be biopsied and examined histologically regardless of the age of the patient.